O uso da negação no português brasileiro: gramática e gramaticalização - Alencar, Dulcelita Pereira Ribeiro de (2009)
This dissertation is within the scope of the actual use of the Brazilian Portuguese, dealing with the negation expressions used by Brazilians. Accordingly, it addresses not only elements of the language system, but also the linguistic variation elements by grammaticalization. The objective hereof is to contribute with grammaticalization studies in the Brazilian Portuguese. The specific purposes are: 1. to analyze the actual use of the negation within the discourse dimension by considering the roles represented by the participants; 2. to verify the actual use within the informativetextual dimension; 3. to address the negation process by differentiating the lexical issues from the grammatical units. The problem dealt with herein is to find out linguistic expressions usually applied in texts and discourses to negate by considering the functional grammatical parameter. The hypotheses set forth herein are the existing difficulties: for the Brazilians is difficulty to say no in view of the cultural aspects. As for the discursive-interaction dimension, the following categories must be regarded: Society, Cognition and Discourse. Within the informative-textual dimension, the relationship between the given information and the new information must be considered according to the informative aspects. The material analyzed is comprised of daily oral dialogs and written texts. This study adopted the analytical-descriptive procedure and considers the dialectic between the social and the individual so as to understand that the systematical grammar is social, as well as the cultural information; the effective use of the individual language producing the system dynamics of the language. The results obtained show that: 1 the negation act falls under the interaction dimension and the use of the negation manners is within the textual-informative dimension; 2. For the Brazilians, to negate the interlocutor s statement is deemed rude; therefore, the lexemes grammaticalization and re-grammaticalization are applied to negate, as a courtesy; 3. The lexemes grammaticalization entails the ressemantização (that is, the establishment of new meanings) of lexemes with cultural implied issues; 4. The re-grammaticalization entails substitution or supplement of the systemic manners. The conclusion hereof is that the negation study is within the scope of the argumentation and entails the social knowledge dynamics